2021
DOI: 10.3390/app11031026
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Rolling Contact Fatigue Behavior in Rails Using Crack Initiation and Growth Models along with Multibody Simulations

Abstract: Rolling contact fatigue (RCF) is a common cause of rail failure due to repeated stresses at the wheel-rail contact. This phenomenon is a real problem that greatly affects the safety of train operation. Preventive and corrective maintenance tasks have a big impact on the Life Cycle Cost (LCC) of railway assets, and therefore cutting-edge strategies based on predictive functionalities are needed to reduce it. A methodology based on physical models is proposed to predict the degradation of railway tracks due to R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…An example of incremental approach application can be found in [27], where the Jiang fatigue damage criterion [28] was utilized. Energy dissipation methods are also applied to predict crack initiation, benefiting from a fast calculation [29]. However, the disadvantage is that the analysis does not provide the characteristics of predicted cracks.…”
Section: Introductionmentioning
confidence: 99%
“…An example of incremental approach application can be found in [27], where the Jiang fatigue damage criterion [28] was utilized. Energy dissipation methods are also applied to predict crack initiation, benefiting from a fast calculation [29]. However, the disadvantage is that the analysis does not provide the characteristics of predicted cracks.…”
Section: Introductionmentioning
confidence: 99%
“…An example of the problem in which a multiaxial stress state occurs is rolling contact fatigue. This phenomenon applies to crane wheels [ 15 ], railway wheels and rails [ 18 , 19 ], rolling bearings [ 20 ], gears [ 21 ], etc. With respect to the crane wheel example, it was shown that not all criteria are suitable for the analysis of elements working in rolling contact conditions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%